Rogue wave fission - Chowdury, Amdad (2022)
We investigate the effect of the third-order dispersion on higher-order rogue wave solutions. We find that under the presence of weak perturbation, the higher-order rogue wave breaks apart into its fundamental rogue wave constituents, similar to how a higher-order soliton undergoes a fission. Each breakaway rogue wave solution is separated in space and time and is accompanied by emission of a dispersive wave.